Blue light–filtering and violet light–filtering hydrophobic acrylic foldable intraocular lenses: Intraindividual comparison. Issue 10 (October 2019) - Nakano, Shinichiro; Miyata, Akira; Kizawa, Junya; Kurosaka, Daijiro; Miyata, Kazunori; Oshika, Tetsuro
Abstract : Purpose : To compare the clinical outcomes after cataract surgery and implantation of a blue light–filtering IOL (AcrySof IQ SN60WF) or a violet light–filtering intraocular lens (IOL) (OptiBlue ZCB00V). Setting : Four surgical sites in Japan. Design : Prospective case series. Methods : One eye of patients with bilateral cataract was randomly allocated to the blue light–filtering IOL and the fellow eye to the violet light–filtering IOL. Visual acuity and contrast sensitivity were assessed over 3 months. The incidence of cyanopsia was evaluated using the neutralization method. Results : The study enrolled 110 eyes of 55 patients. There was no significant difference in visual acuity between the two IOLs. Based on the neutralization results 1 week postoperatively, 15 cases (27.8%) with the light–filtering IOL and 8 cases (14.8%) with the violent light–filtering IOL had cyanopsia; the difference reached statistical significance ( P = .049). After 2 weeks, the difference in the incidence of cyanopsia was not significant. Postoperative contrast sensitivity under photopic condition at 1 week and 3 months and contrast sensitivity under mesopic conditions at 3 months were significantly better with the violet light–filtering IOL than with the blue light–filtering IOL ( P < .05). Conclusions : The violet light–filtering IOL yielded highly satisfactory clinical outcomes, including reduction of cyanopsia and a potential improvement in contrast sensitivity. The different chromophores of the IOL and its different material and design might have contributed.